Hydroeconomic optimization of integrated water management and transfers under stochastic surface water supply - Zhu, Tingju; Marques, Guilherme Fernandes; Lund, Jay R. (American Geophysical Union, 2015)
Efficient reallocation and conjunctive operation of existing water supplies is gaining importance as demands grow, competitions among users intensify, and new supplies become more costly. This paper analyzes the roles and benefits of conjunctive use of surface water and groundwater and market‐based water transfers in an integrated regional water system where agricultural and urban water users coordinate supply and demand management based on supply reliability and economic values of water. Agricultural users optimize land and water use for annual and perennial crops to maximize farm income, while urban users choose short‐term and long‐term water conservation actions to maintain reliability and minimize costs. The temporal order of these decisions is represented in a two‐stage optimization that maximizes the net expected benefits of crop production, urban conservation and water management including conjunctive use and water transfers. Long‐term decisions are in the first stage and short‐term decisions are in a second stage based on probabilities of water availability events. Analytical and numerical analyses are made. Results show that conjunctive use and water transfers can substantially stabilize farmer's income and reduce system costs by reducing expensive urban water conservation or construction. Water transfers can equalize marginal values of water across users, while conjunctive use minimizes water marginal value differences in time. Model results are useful for exploring the integration of different water demands and supplies through water transfers, conjunctive use, and conservation, providing valuable insights for improving system management.